2004
DOI: 10.1038/sj.mp.4001541
|View full text |Cite
|
Sign up to set email alerts
|

Linkage analysis of psychosis in bipolar pedigrees suggests novel putative loci for bipolar disorder and shared susceptibility with schizophrenia

Abstract: The low-to-moderate resolution of linkage analysis in complex traits has underscored the need to identify disease phenotypes with presumed genetic homogeneity. Bipolar disorder (BP) accompanied by psychosis (psychotic BP) may be one such phenotype. We previously reported a genome-wide screen in a large bipolar pedigree sample. In this follow-up study, we reclassified the disease phenotype based on the presence or absence of psychotic features and subgrouped pedigrees according to familial load of psychosis. Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
111
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(130 citation statements)
references
References 33 publications
15
111
1
2
Order By: Relevance
“…12,13,19,20,[60][61][62] They are especially interesting as the same regions may encompass susceptibility genes for schizophrenia. [63][64][65][66][67][68][69][70] Park et al 71 made similar conclusions in a study of psychotic BD in which most areas of linkage overlapped with those reported in previous investigations of schizophrenia.…”
Section: Psychotic Symptoms In Bdsupporting
confidence: 77%
“…12,13,19,20,[60][61][62] They are especially interesting as the same regions may encompass susceptibility genes for schizophrenia. [63][64][65][66][67][68][69][70] Park et al 71 made similar conclusions in a study of psychotic BD in which most areas of linkage overlapped with those reported in previous investigations of schizophrenia.…”
Section: Psychotic Symptoms In Bdsupporting
confidence: 77%
“…38 Another group reported genome-wide significant linkage to BP with psychosis on chromosomes 9q31 and 8p21. 39 That same group studied a separate sample and found genome-wide significant linkage to BP with psychosis on chromosome 16p12. 17 Several of these loci fall within regions that have been implicated in previous studies of BP and schizophrenia.…”
Section: Discussionmentioning
confidence: 98%
“…3 A total of 36 of these families are included in the 'psychosis' category, as described. 1 Best-estimate consensus diagnoses are based on the Research Diagnostic Criteria (RDC) 4 using all available sources of information. The models used for the broadened affected phenotype, or 'all BP', are the same as those employed in our initial genome scan 3 : BP1 (manic syndromes; mostly BPI disorder), BP2 (BP1 plus BPII disorder), and BP3 (BP2 plus recurrent major depression).…”
mentioning
confidence: 99%
“…The corresponding models for psychotic BP are BP-P1, BP-P2, and BP-P3 described elsewhere. 1 They include 68, 72, and 79 affected individuals, respectively. Thus, the broadened psychotic BP sample includes an additional 228 nonpsychotic affected individuals.…”
mentioning
confidence: 99%